The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Volume 4: Cycle Innovations; Fans and Blowers; Industrial and Cogeneration; Manufacturing Materials and Metallurgy; Marine; Oil 2011
DOI: 10.1115/gt2011-46210
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Compressor Cascade Washing for Gas Turbine Performance Investigation

Abstract: On-line compressor washing for industrial gas turbine application is a promising method of mitigating the effects of compressor fouling degradation; however there are still few studies from actual engine experience that are inconclusive. In some cases the authors attribute this uncertainty as a result of other existing forms of degradation. The experimental approach applied here is one of the first of its kind, employing on-line washing on a compressor cascade and then relating the characteristics to a three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
2
7
0
1
Order By: Relevance
“…Larsson et al [36] found out that, for a mechanical drive site, the deviation from the nominal reference value of compressor efficiency and mass flow due to fouling could be up to 3% and 2% respectively over a time frame of 13 days, but, after compressor wash, the degradations are partially restored by about 2%. In particular, with regard to performance recovery, Igie et al [22] state that an optimistic recovery of 50% of the lost power and of all the key parameters can be obtained after compressor washing [22]. Therefore, scenarios #1 through #4 reproduce all these different situations.…”
Section: Discussion On the Degradation Scenariosmentioning
confidence: 95%
See 2 more Smart Citations
“…Larsson et al [36] found out that, for a mechanical drive site, the deviation from the nominal reference value of compressor efficiency and mass flow due to fouling could be up to 3% and 2% respectively over a time frame of 13 days, but, after compressor wash, the degradations are partially restored by about 2%. In particular, with regard to performance recovery, Igie et al [22] state that an optimistic recovery of 50% of the lost power and of all the key parameters can be obtained after compressor washing [22]. Therefore, scenarios #1 through #4 reproduce all these different situations.…”
Section: Discussion On the Degradation Scenariosmentioning
confidence: 95%
“…Therefore, scenarios #1 through #4 reproduce all these different situations. Scenarios #5 and #6 are also considered in this paper to account for a considerable decrease of 10% of the parameter Q(t), since fouling can cause an 8.7% reduction in power over a one-year period [22]. Recovery is instead assumed the same as in scenarios #1 through #4.…”
Section: Discussion On the Degradation Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common measures to reduce fouling are compressor washing and inlet filter exchange. Among the many papers produced on fouling effects, the following specifically deal with the time evolution of compressor fouling and its effects over time on gas turbine performance [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Se han realizado amplios estudios sobre lavados on-line (Igie et al (2011), Syverud (2007 o Schneider (2010)). En ellos se explica que el lavado on-line se realiza normalmente con la turbina funcionando a plena carga y por lo tanto, con los VIGVs abiertos del todo.…”
Section: Lavados On-lineunclassified